A Few Remarks on the Description of the Baptism of the Emperor Constantine in the Chronicle of George the Monk, Actus Silvestri, and the Byzantine Hagiographical Tradition1 - Rafał Kosiński (Classica Cracoviensia)
This article focuses on the 9th century accounts of Constantine I’s baptism. Sources from this period strongly reject Eusebius of Caesarea’s account of Constantine’s baptism on his deathbed and promote the tradition of the emperor’s baptism at the hands of Pope Sylvester in Rome in the early years of the emperor’s reign. The acceptance of the legend of Pope Sylvester seems to be connected with the idea of Emperor Constantine’s personal holiness in opposition to the emperors’ promotion of the emperor-priest ideal in the 8th century. However, the acceptance of the legend concerning Pope Sylvester may also be related to the perception – during the iconoclasm period – of the papacy as a bastion of orthodoxy.